2007
DOI: 10.1073/pnas.0608144104
|View full text |Cite
|
Sign up to set email alerts
|

Association of parameter, software, and hardware variation with large-scale behavior across 57,000 climate models

Abstract: In complex spatial models, as used to predict the climate response to greenhouse gas emissions, parameter variation within plausible bounds has major effects on model behavior of interest. Here, we present an unprecedentedly large ensemble of >57,000 climate model runs in which 10 parameters, initial conditions, hardware, and software used to run the model all have been varied. We relate information about the model runs to large-scale model behavior (equilibrium sensitivity of global mean temperature to a doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 17 publications
0
66
0
Order By: Relevance
“…The PBL mass budget leads to the direct proportionality between the PBL depth, h, and the entrainment rate (Medeiros et al, 2005). Knight et al (2007) reported the highest climate sensitivity for the lowest A, found in the shallowest PBL. The reciprocal relationship between the climate sensitivity and the PBL depth suggests larger climate variability in stably stratified boundary layers (Esau, 2008;Zilitinkevich and Esau, 2010), where h is small, typically less than 200 m in nocturnal PBL as to be compared to its daytime counterpart with h > 1000 m (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PBL mass budget leads to the direct proportionality between the PBL depth, h, and the entrainment rate (Medeiros et al, 2005). Knight et al (2007) reported the highest climate sensitivity for the lowest A, found in the shallowest PBL. The reciprocal relationship between the climate sensitivity and the PBL depth suggests larger climate variability in stably stratified boundary layers (Esau, 2008;Zilitinkevich and Esau, 2010), where h is small, typically less than 200 m in nocturnal PBL as to be compared to its daytime counterpart with h > 1000 m (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Knight et al, 2007), which excurse beyond the current narrow focus on PBL parameterizations in climate models. Using a classification and regression tree approach, Knight et al (2007) demonstrated with 57 067 climate model HadAM3 runs that 80% of variation in climate sensitivity to 2 × CO 2 is associated with variation of a small subset of parameters mostly related to the convection proCorrespondence to: I. Esau (igore@nersc.no) cesses.…”
Section: Introductionmentioning
confidence: 99%
“…climate model optimization | metamodeling | precipitation bias and sensitivity I nterest in systematic parameter sensitivity and optimization has been developing both in the context of global average climate sensitivity associated with increased greenhouse gases and the effort to improve the model climatology (1)(2)(3)(4)(5)(6)(7). Some of this work has focused on variations with parameter of a climate sensitivity defined by the change of global average surface temperature under doubled CO 2 , some on optimizing the simulation of current climate features by tuning parameter values.…”
mentioning
confidence: 99%
“…Uncertainties in model predictions can, and do, arise from structural simplifications such as these (Smith 2002;Stainforth et al 2007). In highly complex global climate models, uncertainties also arise from parametrizations ('knob settings') and inherent chaotic behaviour, both of which may be tackled without specific geological hindsight (Stainforth et al 2005(Stainforth et al , 2007Knight et al 2007). However, if we are to assess the degree to which model truncations may result in qualitatively impaired behaviour, access to independent historical information is imperative.…”
Section: (C ) Model Testingmentioning
confidence: 99%